Anti-Corruption Culture: Reforms And Main Directions Socio-Philosophical Analysis (Texas Journal of Multidisciplinary Studies, 2022)
Corruption as a phenomenon has been familiar to people since ancient times. It is not one of the oldest, but it is also not a relatively young phenomenon of social reality. For about seven centuries, history has taught us that in the course of civilization mankind has been quite successful in fighting this evil. But even at the beginning of the third millennium, we humans have not yet succeeded in eradicating corruption in the full sense of the word. Corruption is a self-perpetuating phenomenon that exists within public life and has no national or territorial borders. This concept testifies to its imperfection and weakness and arises from the "bowels" of the state, the low legal culture of not only officials, but also society as a whole. After all, officials are a part of society. At the same time, corruption is one of the elements of the "legal" shadow life.